Éster 2-morfolinoetil e sal sódico do ácido micofenólico : desenvolvimento e validação de métodos analíticos para o controle de qualidade de matéria-prima e comprimidos. - Andre Lima de Oliveira Costa (2009)
Mycophenolic acid (MPA) is a specific, non-competitive and reversible inhibitor of inosine monophosphate dehydrogenase. It is marketed as pro-drug mycophenolate mofetil (MMF) in immediate release tablets, as well as sodium mycophenolic (MSD) in enteric-coated tablets formulation. The derivatives of MPA are used in the immunosuppression therapy of post-transplant patients. The evaluation of the qualityparameters for drug substance and tablets containing the derivatives of MPA is important to surveillance actions, regulatory matters and to promote national manufacturing by the public official laboratories. The quality of MMF drug substance was evaluated according to physicalchemical tests described in European Pharmacopoeia. An assay method for MMF and its degradation products (hydrolysis) in tablets using high performance liquid chromatography was developed and validated. Alternative method by ultraviolet spectrophotometry was used to assayMMF in tablets. The methods were equivalent on precision and accuracy, however, the spectrophotometric method is not selective for impurities. The dissolution profile of MMF tablets was evaluated using generic and reference drugs at different conditions (HCl 0.1 mol/l, HCl 0.01 mol/l and phosphate buffer 0.1 mol/l pH 3.0) with paddles 50 rpm. Both products showed dissolution (n = 12) greater than 85% in 15 minutes, demonstrating that the drug is easily released by formulations.Physicalchemical tests concerning the identity, purity and assay for analysis of MSD drug substance was proposed. A method using high performance liquid chromatography was developed and validated to assay MSD in drug substance and tablets. A method by ultraviolet spectrophotometry was also developed and validated to assay MSD in tablets, and showed the same precision and accuracy compared tothe chromatography method. The resistance of the enteric coating tablets at gastric fluid was checked qualitatively on disintegration test and quantitatively on dissolution test. The release of the drug was evaluated in phosphate buffer solution at pH 5.5 , 6.0 and 6.8. Pharmacopoeial monographs were proposed for MMF and MSD drug substance and tablets based on the obtained experimental data.